The damaging effect of surface-traffic-generated soil pressures on buried archaeological artefacts - Dain-Owens, Anne Peregrine (Cranfield University, 2010)
The aim of this work was to investigate the influence of surface loading from conventional field operations on the damage to buried artefacts, both pots and bones. The objectives of this research were a) to investigate the influence of surface loading and resulting breakage relating to the material strengths of buried objects - ceramic (unglazed), and aged bone; b) to assess the magnitudes of peak subsurface pressures transferred through soil under the dynamic surface loading from tyres and other field operations; c) to develop and test an empirical model for predicting the effects of subsurface pressure application on buried objects from surface loads; and d) to explore ways of identifying the potential for damage to buried artefacts under agricultural and other field operations. Experimental investigations were performed in both the laboratory and field. The laboratory work was undertaken to determine the magnitude of subsurface pressure at which buried objects were damaged. Conducted in a sandy-loam-filled soil bin, instrumented ceramic and bone artefacts were buried alongside pressure sensors and subjected to loading by a single smooth tyre appropriately loaded and inflated for subsurface pressure generation. The breakage of the buried objects and the pressures under the moving tyre were recorded in order to allow correlation of the subsurface pressures to buried artefact breakage. The fieldwork was done to determine the magnitudes of subsurface pressure generated by individual field operations whilst travelling in a similar sandy loam field soil. Four plots were established, with each assigned a particular cultivation regime. An accelerated timeframe was utilized so that a years’ series of field operations could be driven over pressure sensors buried in the soil. The peak pressures from each field operation within each plot were recorded and summarized, and the data was analysed relative to field operation type and cultivation regime type. Multiple statistical analyses were performed, as the laboratory data and field data were independently evaluated before being correlated together. An empirical relationship between buried object damage and subsurface pressure magnitude was developed. The different pot types and bone orientations broke at different subsurface pressures. The four pot types listed in ascending order of strength to resist damage (with breakage pressure threshold value) are: shell tempered (1.3 bar), grog tempered (1.6 bar), flint tempered (3.1 bar), and sand tempered (3.6 bar). Aged human radius bones were tested, and the parallel bone orientation proved stronger than the perpendicular orientation, where 2.8 bar was the lowest subsurface pressure found to cause damage. The primary field operations, presented in ascending order relative to peak magnitude of subsurface pressure per specific operation, are: roll (0.68 bar), drill (1.03 bar), heavy duty cultivator (1.21 bar), spray 1 (1.27 bar), harvester (1.30 bar), spray 2 (1.31 bar), tractor / trailer (1.46 bar), shallow mouldboard plough (1.61 bar), deep mouldboard plough (2.04 bar). The relationships between vehicle specification and subsurface pressure generation potential were described, relating to the vehicle mass, tyre/track physical properties, and tyre inflation pressure. The effect of cultivation method on overall magnitude of subsurface pressure was defined, with lowest pressure generation within a zero-till cultivation regime (1.08 bar), higher in a non-inversion cultivation regime (1.13 bar), followed by the shallow inversion regime (1.22 bar), and highest within a conventional inversion scheme (1.30 bar). The laboratory and field results were correlated by a statistical analysis comparing breakage point to peak subsurface pressure. The shell tempered pot was found to be most susceptible to damage. The grog tempered pot was less vulnerable to damage, followed by the flint tempered pot. The quartz tempered pot was predicted to survive intact under all field operations within this research. In conclusion, this research has developed a functional and predictive empirical relationship between damage to pot and aged bone artefacts from subsurface soil pressures generated by surface traffic. It has been found that different types of buried pot and bone artefacts break at different subsurface pressures. In addition, a complete dataset consisting of peak subsurface pressures recorded under a year’s range of field operations within a sandy loam soil at field-working moisture content has been compiled. The effect of different cultivation methods on the generation of subsurface pressures was also evaluated. The breakage thresholds specific to each artefact type have been related to the in-field subsurface soil pressures. A correlation of breakage to the subsurface pressures under each operation yields a prediction of percentage of artefact-type breakage. From this correlation, relationships are observed between vehicle specification, subsurface pressure generation, and consequential artefact breakage. The achievements provide knowledge about how field operations affect specific types of buried archaeology, providing a valuable asset to farmers, land managers, and regulatory bodies. It is evident that agricultural practices, choice of track or tyre type, and inflation pressures must be carefully managed if the intention is to protect or mitigate damage to buried archaeological artefacts. Thus, a contribution has been made to the development of ‘best management practices’ and to the specification and use of field operations relative to intended mitigation of buried artefact damage.